London - Stara, Alexandra (2003)
Texto analítico de Londres basado en tres proyectos fotográficos de Rut Blees Luxemburg
Keywords: URBANISMO; ARTE; FOTOGRAFIA; INGLATERRA; LONDRES; BLEES LUXEMBURG, RUT; CRITICA